A Multimodal Critical Discourse Analysis of Samsung’s Ingenius, Website, Consumers’ Comments, and Samsung-Apple Brand Positioning - Marcella Evelyn (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study analyzed Ingenius video advertisement. Ingenius is a video advertisement produced by Samsung. However, Samsung only shows its competitor’s product (Apple IPhone X) from the beginning until the end of the video. The video is divided into seven segments and was analyzed by using both Multimodal Discourse Analysis and Critical Discourse Analysis three-dimension framework by Fairclough. This study is expected to find how the Apple IPhone X is represented by Samsung in their Ingenius video advertisement, to find the Ingenius messages according to Samsung’s website, to see the reaction of its consumers, and to find how the brand positioning of Samsung and Apple in the society. Multimodal Discourse Analysis is used to analyze the inner dimension of the framework by using Ingenius video advertisement as the text or discourse. The second dimension is analyzed by using the official Samsung explanation from its website about the video to see the meaning of each segment from the producer to consumers and using the YouTube comments to see how the consumers of the video (viewers) react after watching the video. The outer dimension sees the brand positioning from online newspapers, websites, and blogs to see how the society perceives Apple and Samsung as smartphone brands. Keywords: Multimodal Discourse Analysis (MDA), Critical Discourse Analysis (CDA), Advertisements, Discourse.